Investigating the Cytotoxic Effects of Aminoglycosides on A549 Lung Cancer Cell Line - Karthikeyan M; Praveen B M (The Bioscan, 2025)
Objective: The current study was carried out to evaluate the cytotoxicity activity of aminoglycosides, specifically amikacin and gentamicin, on human lung cancer cell lines. Methods: Cytotoxicity activity was evaluated on human cancer cell lines such as lung cancer (A549) using the MTT assay method. Results: The selected aminoglycosides showed dose-dependent cytotoxicity activity on the tested cell lines. Variations in cytotoxicity were observed on different cell lines for the tested aminoglycosides. The cytotoxicity of the aminoglycosides increased as their concentration increased. Among the tested aminoglycosides, gentamicin showed better cytotoxicity activity on the tested cell lines. Conclusion: The results of the present study suggest that amikacin and gentamicin have bioactive constituents with cytotoxic properties and their isolation can be useful for developing new anticancer drugs.